Digital design : principles and practices. - Wakerly, John F., ....- (Upper Saddle River : Pearson, 2006)
Blends academic precision and practical experience in an authoritative introduction to basic principles of digital design and practical requirements. With over 30 years of experience in both industrial and university settings, the author covers the most widespread logic design practices while building a solid foundation of theoretical and engineering principles for students to use as they go forward in this fast moving field.
Keywords: Digitale technieken